Study of adsorption of phosphate ions from aqueous solutions - Obushenko, Tetiana; Tolstopalova, Nataliia; Sanginova, Olga; Kostenko, Evgeniy; Bolielyi, Oleksandr; Kurylenko, Viktor (Technology audit and production reserves, 2022)
The object of research in this work is model aqueous solutions containing phosphate ions. Phosphorus is an essential nutrient for all life forms and determines the trophic state of freshwater ecosystems. The existing problem is that when excessive phosphorus enters water bodies, it causes their eutrophication, and, as a result, the accumulation of biotoxins, deterioration of water quality, death of aquatic organisms, etc. Phosphorus comes to surface water from domestic wastewater containing phosphates as components of synthetic detergents, photoreagents and water softeners. A significant contribution is made by the washout of phosphate fertilizers and pesticides from agricultural land, and runoff from livestock farms and industrial enterprises. Among the methods of wastewater treatment from phosphates, a special place is occupied by sorption. An analysis of modern scientific publications on this topic shows that the search for new effective sorbents obtained using resource-saving technologies is an important scientific and practical problem. The work was aimed precisely at the search for such sorbents. Iron is known to have a high affinity for phosphate. Therefore, the paper proposes to use the sediments of groundwater iron removal stations as a sorbent. These sludges are produced in significant quantities and create significant environmental problems. The sorption of iron-containing sorbent, which is a waste of iron removal stations with respect to phosphate ions, has been studied. It has been established that this sorbent is effective for extracting phosphate ions from water with an adsorption capacity of 72.67 mg/g. The sorption process is quite accurately described by the pseudo-second order sorption kinetic equation (determination coefficient R2=0.9737). The rate constant of the sorption process was calculated to be 3.8·10–4 g/mg PO43–·min1/2. The use of the proposed sorbent will allow solving two environmental issues: replenishment of the list of cheap effective sorbents for removing phosphates and utilization of sludge from iron removal stations.